Pengaruh Penambahan Susu Bubuk Fullcream Terhadap Mutu Produk Minuman Fermentasi dari Ekstrak Ubi Jalar Merah (Ipomoea batatas L) - Novelina, Novelina; Eliyasmi, Rifma; Ariani, Siska; Firdausni, Firdausni (Jurnal Litbang Industri, 2012)
This study was aimed to find exact volume of fullcream milk powder which added in the fermented beverage of red sweet potatoes extract (Ipomoea batatas L), as well as to investigate physical and chemical characteristics, and organoleptic. So it was obtained the fermented beverages which fulfilled the quality requirements of yogurt according to SNI 01- 2981-1992. Analysis was conducted on total Lactobacillus, total plates count, total lactic acid, pH, total solids, viscosity, and fat content. Organoleptic test of the color, texture, flavor, consistency, and taste was also carried out. The best product was analyzed for the chemical properties such as protein content, ash and crude fiber. The design used in this study was completely randomized design (CRD) with four treatments of fullcream milk powder addition 5%, 10%, 15% and 20% respectively with 3 replications. The organoleptic test of the most preferred by the panelists was a fermented beverage with the addition of 10% fullcream milk powder. This product contained Lactobacillus total; 7.3 x 108 CFU/ml, total plate count; 1.4 x 107 CFU/ml, total lactic acid; 1.56%, pH; 4.42, total solids; 25.62%, viscosity; 25.5 dPa.s, fat content; 3.4%, protein content; 6.34%, ash content; 0.11%, and crude fiber content; 0.17%.ABSTRAKPenelitian ini bertujuan untuk mengetahui jumlah penambahan susu bubuk fullcream yang tepat pada minuman fermentasi ekstrak ubi jalar merah (Ipomoea batatas L), sertakarakteristik fisik, kimia dan organoleptik, sehingga diperoleh minuman fermentasi dariekstrak ubi jalar merah yang memenuhi persyaratan mutu yogurt menurut SNI 01 - 2.981- 1.992. Analisis dilakukan pada total Lactobacillus, angka lempeng total, asam laktat total, pH, total padatan, viskositas, kadar lemak dan organoleptik warna ,tekstur, rasa, konsistensi, rasa. Produk terbaik yang didapatkan dianalis sifat kimia seperti kadar protein, abu dan serat kasar. Rancangan yang digunakan dalam penelitian ini adalah rancangan acak lengkap (RAL) dengan 4 perlakuan penambahan susu bubuk fullcream 5%, 10%, 15% dan 20% dan 3 kali ulangan. Uji organoleptik yang paling disukai oleh panelis adalah perlakuan penambahan susu bubuk fullcream 10%. Produk ini mengandung Lactobacillus total dari 7,3 x 108 CFU / ml, angka lempeng total 1,4 x 107 CFU / ml, asam laktat sebesar 1,56%, pH 4,42, total padatan 25,62%, 25,5 dPa.s viskositas, kandungan lemak 3,4%, kadar protein 6,34%, kadar abu 0,11%, kadar serat kasar 0,17%.